Targeting Inflammation-Induced Immune Evasion in Colorectal Cancer: Zinc Pyrithione Downregulates PD-L1 Expression to Restore Antitumor Immunity - V BRAHMAIAH,; G DEEPTHI REDDY,; B Y KAVITHA,; Dr G DEEPIKA, (The Bioscan, 2025)
Background: Colorectal cancer is adept at modulating immune responses, particularly in the context of chronic inflammation, with immune evasion being a critical factor in its progression. Inflammation can induce the expression of Programmed Death-Ligand 1, leading to T cell inactivation and tumor immune escape. Zinc Pyrithione has demonstrated anti-inflammatory and anticancer properties; however, its potential to modulate immune checkpoint pathways and restore immune function under inflammatory conditions remains largely unexplored. This study investigates the immunomodulatory role of ZnPT in counteracting inflammation-induced immune escape in colorectal cancer. Methods: In vitro experiments were conducted using HT-29 and SW480 colorectal cancer cell lines to simulate an inflammation-induced immunosuppressive tumor microenvironment. Cells were stimulated with lipopolysaccharide to induce inflammation, followed by treatment with ZnPT. PD-L1 expression was assessed at both mRNA and protein levels. A co-culture model with peripheral blood mononuclear cells was employed to evaluate the impact of ZnPT on immune cell-tumor interactions, with interferon-gamma secretion quantified via ELISA as a measure of immune activation. Results: LPS stimulation significantly increased PD-L1 expression in colorectal cancer cells, confirming the induction of an immune escape phenotype. Subsequent treatment with ZnPT effectively restored IFN-γ secretion in PBMC co-cultures, indicating a reversal of inflammation-induced immune suppression. In HT-29 cells, LPS exposure reduced IFN-γ levels, but ZnPT treatment led to a dose-dependent increase in IFN-γ secretion. Similarly, in SW480 cells, IFN-γ levels decreased after LPS treatment, but ZnPT administration elevated IFN-γ production. Conclusion: ZnPT can modulate PD-L1 expression and enhance immune responsiveness in the tumor microenvironment. These findings suggest the potential of ZnPT as a therapeutic agent for reversing immune suppression and restoring effective anti-tumor immune responses in colorectal cancer.